Nonclinical phenotypic and genotypic analyses of a Phase 1 pediatric respiratory syncytial virus vaccine candidate MEDI-559 (rA2cp248/404/1030ΔSH) at permissive and non-permissive temperatures - Schickli, Jeanne H.; Kaur, Jasmine; Tang, Roderick S. (Virus research, 2012)
► RSV vaccine MEDI-559 has 39 nt silent differences compared to a previous candidate. ► Variants of temperature-sensitive (ts) MEDI-559 can occur at elevated temperatures. ► Most variants involved changes at one or two ts markers called 248 and 1030. ► One variant maintained all ts and cp markers and had 2 novel changes in polymerase. ► All variants were highly attenuated in cotton rats. MEDI-559 is a recombinant live attenuated intranasal RSV vaccine candidate currently being evaluated in 5 to <24 month old RSV seronegative infants for safety and immunogenicity. MEDI-559 and the previously tested rA2cp248/404/1030ΔSH both have 5 cold-passaged mutations, 3 temperature sensitive (ts) markers designated 248, 404, and 1030, and deletion of the SH gene that collectively contribute to their attenuation and temperature sensitive growth phenotypes. However, MEDI-559 differs from rA2cp248/404/1030ΔSH by 39 silent nucleotide substitutions. Nevertheless, these viruses have comparable in vitro and in vivo phenotypes. Temperature sensitivity is monitored by the efficiency of plaque formation at elevated temperatures. The efficiency of plaque formation of MEDI-559 is reduced by ≥100-fold at 35°C and by ≥1000 fold at 37°C compared to 32°C. Passaging of MEDI-559 at temperatures up to 37°C resulted in generation of temperature sensitive intermediate (tsi) viruses. The most frequent change was a reversion to wildtype tyrosine at the 1030 ts site followed by a less frequently observed leucine to non-wildtype serine substitution at the 248 ts site. One tsi virus had changes at both the 248 and 1030 ts sites and another tsi virus that had maintained all of the 248, 404 and 1030 ts sites had two novel changes (Asp158Gly and Ser1313Cys) in the polymerase (L) gene. Asp158Gly and Ser1313Cys singly or in combination in the MEDI-559 genetic background were confirmed to result in a tsi growth phenotype. All the tsi viruses have small plaque phenotypes and are highly attenuated in the lungs of cotton rats.